Race, Socioeconomic Status, and Age: Exploring Intersections in Preterm Birth Disparities among Teen Mothers. (12th February 2015) - Coley, Sheryl L.; Nichols, Tracy R.; Rulison, Kelly L.; Aronson, Robert E.; Brown-Jeffy, Shelly L.; Morrison, Sharon D.
Abstract : Few studies have examined disparities in adverse birth outcomes and compared contributing socioeconomic factors specifically between African-American and White teen mothers. This study examined intersections between neighborhood socioeconomic status (as defined by census-tract median household income), maternal age, and racial disparities in preterm birth (PTB) outcomes between African-American and White teen mothers in North Carolina. Using a linked dataset with state birth record data and socioeconomic information from the 2010 US Census, disparities in preterm birth outcomes for 16, 472 teen mothers were examined through bivariate and multilevel analyses. African-American teens had significantly greater odds of PTB outcomes than White teens (OR = 1.38, 95% CI 1.21, 1.56). Racial disparities in PTB rates significantly varied by neighborhood income; PTB rates were 2.1 times higher for African-American teens in higher income neighborhoods compared to White teens in similar neighborhoods. Disparities in PTB did not vary significantly between teens younger than age 17 and teens ages 17–19, although the magnitude of racial disparities was larger between younger African-American and White teens. These results justify further investigations using intersectional frameworks to test the effects of racial status, neighborhood socioeconomic factors, and maternal age on birth outcome disparities among infants born to teen mothers.